COMPARATIVE EVALUATION OF SEROLOGICAL ASSAYS FOR DENV DIAGNOSIS IN PRIMARY AND SECONDARY INFECTIONS - Dr Tariq Aziz; Dr Shahid Ali; Dr Mahnoor Ghaffar; Dr Sheharyar Abid; Dr Sumeet Kumar; Dr Pirya Bai (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Dengue virus or DENV and belong to the Flaviviridae family is still an important public health problem worldwide and as a result of the bite of Aedes aegypti mosquito. Definitive diagnosis is important specially to differentiate DENV from other etiologies of fever and to control disease management and prevention strategies. This work was planned to assess the diagnostic capability of the range of assays of serological methods that can identify DNA and RNA, and PRNT in differentiating primary and secondary DENV infections.Methodology: For the 2023 dengue outbreak, a study design was set on 500 febrile patients. Blood specimens were obtained at various days since symptom onset (days 1-3, 4-7, 8-14, and >15) and tested for IgM- MAC-ELISA and IgG-ELISA, and viral RNA load, and NS1 antigen. PRNT was used as the reference assay. Sensitivity, specificity and PPVs of each assay were determined and analyzed using statistical package-SPSS version 27.Results: Recent infection identification was accurate in 80 percent of primary IgM identification after day 4, but secondary IgM identification was only 45 percent sensitive. Increased IgG by day 10 in both types of infection made it difficult to differentiate between them. The NS1 antigen was positive in 85% of the cases in first five days and in only 40% cases by days 10. RT-PCR was 95% sensitive during day 1 to 7 but negative from day 10 onward because of low virus load in the sera. PRNT had 98% overall accuracy when it comes to discerning between the primary and secondary infections. Specific complications of the secondary included early sharp increase in IgG titration by day 7 and cross-reactivity with other flaviviruses in 15% cases.Conclusion: The results provided insight into the problems of utilizing serological assays in diagnosing secondary infections and thus, the necessity of utilizing nucleic acid detection and PRNT simultaneously. This work highlights the need for the identification of the appropriate diagnostic methods depending on the stage of the infection and calls for using modern methods, including machine learning, for the analysis of the results. We recommend that future studies examine the specificity of the assays and look at antibody dynamics past the 90-day marker. These finding are crucial for better identification and enhancement of diagnostic procedures and outbreak containment measures.